Analysis of Delayed Notification of Acquisition of Shares by Business Players Using the Cost Benefit Analysis and Regulatory Impact Analysis Methods - Ani Ani (Jurnal Indonesia Sosial Sains, 2023)
Business Competition Law in Indonesia adheres to a post-notification system which is carried out after the effective date in the process of taking over (mergers and acquisitions) of a company. Based on data on the KPPU's website, during the period from 2012 – 2022 there were 45 cases of fines for late notification in the merger and acquisition process with a total fine of Rp. 118,765,000,000. Data on company acquisition case decisions from 11 February 2020 to 11 April 2021, found delays in notifications of mergers and acquisitions with delays ranging from 2 (two) days to more than 8 (eight) years. One of the mitigating reasons in the KPPU's decision was the ignorance of business actors regarding the obligation to submit post-notification of company takeover to KPPU. In order to avoid this problem, in the future, it is expected that KPPU or the Government can amend the provisions concerning post-notification obligations to become pre-notification obligations.